Pelatihan Membuat Media Persepsi Taktil Pada Guru-Guru di SLB YPPLB 2 Makassar - Bastiana, Bastiana; Sulasminah, Dwiyatmi; Rahmi, Nurazizah; Kasmawati, St.; Syawaluddin, Ahmad (PORTAL RISET DAN INOVASI PENGABDIAN MASYARAKAT, 2024)
Children with special needs in their learning require a different approach or method of learning from children in general. This tactile perception media making training aims to improve the skills of teachers in SLB YPPLB 2 Makassar in designing and making appropriate media for students with special needs, especially those with sensory limitations such as blind children and autistic children. Tactile media functions as a learning aid based on the sense of touch, enabling students to understand the concepts and shapes of flat shapes and numbers through sensory experiences. This program is implemented through three stages: preparation, implementation, and post-training assistance. The implementation stage includes an introduction to the concept of tactile perception, the practice of making media, and simulation of its use in the classroom. In addition, mentoring and evaluation are conducted to ensure sustainable implementation in the classroom. The training results showed significant improvement in teachers' skills in creating and using tactile media. Teachers also successfully integrated the media into the curriculum, creating more inclusive learning. The success of the training is supported by teachers' enthusiasm and support from the school, although there are still obstacles such as limited teacher time and technology resources. Overall, this training has a positive impact in improving the quality of learning for students with special needs in SLB YPPLB 2 Makassar. It is recommended that schools provide special time for teachers to develop media and collaborate with external parties to procure additional resources.